Progenitor-Based Cell Biological Aspects of Neocortex Development and Evolution - Vaid, Samir; Huttner, Wieland B. (Frontiers in Cell and Developmental Biology, 2022)
During development, the decision of stem and progenitor cells to switch from proliferation to differentiation is of critical importance for the overall size of an organ. Too early a switch will deplete the stem/progenitor cell pool, and too late a switch will not generate the required differentiated cell types. With a focus on the developing neocortex, a six-layered structure constituting the major part of the cerebral cortex in mammals, we discuss here the cell biological features that are crucial to ensure the appropriate proliferation vs. differentiation decision in the neural progenitor cells. In the last two decades, the neural progenitor cells giving rise to the diverse types of neurons that function in the neocortex have been intensely investigated for their role in cortical expansion and gyrification. In this review, we will first describe these different progenitor types and their diversity. We will then review the various cell biological features associated with the cell fate decisions of these progenitor cells, with emphasis on the role of the radial processes emanating from these progenitor cells. We will also discuss the species-specific differences in these cell biological features that have allowed for the evolutionary expansion of the neocortex in humans. Finally, we will discuss the emerging role of cell cycle parameters in neocortical expansion.